2020
DOI: 10.1002/arco.5207
|View full text |Cite
|
Sign up to set email alerts
|

A different paradigm for the initial colonisation of Sahul

Abstract: The questions of when and how humans reached Sahul, the Pleistocene continent of Australia and New Guinea, has remained a central issue of Australian archaeology since its development as an academic discipline in the mid-twentieth century. Modelling this event has persistently appealed to minimal assumptions -the simplest watercraft, the shortest routes, the smallest viable colonising groups. This paper argues that Australian archaeology can no longer ignore the way our understanding of this initial colonisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 90 publications
0
24
0
Order By: Relevance
“…Recent mutation rate studies have also suggested significantly slower annual rates than previously estimated (Besenbacher et al . 2018; Scally 2016) which would consequently push back divergence dates such as those discussed by Allen and O'Connell (2020). While these rate studies are based on genome‐wide calculations, and not focused on mitochondrial DNA (Tobler et al .…”
Section: Commentsmentioning
confidence: 89%
See 4 more Smart Citations
“…Recent mutation rate studies have also suggested significantly slower annual rates than previously estimated (Besenbacher et al . 2018; Scally 2016) which would consequently push back divergence dates such as those discussed by Allen and O'Connell (2020). While these rate studies are based on genome‐wide calculations, and not focused on mitochondrial DNA (Tobler et al .…”
Section: Commentsmentioning
confidence: 89%
“…Allen and O'Connell (2020) present a critique of minimalist assumptions, such as the favouring of shortest water crossings, in early human settlement models of Australia and New Guinea. While criticism of these assumptions is hardly new (Jones 1968), they nonetheless lie at the heart of most current discussion.…”
Section: Commentsmentioning
confidence: 99%
See 3 more Smart Citations